O-2 Cancer related insomnia: wireless monitoring of sleep metrics. (1st March 2017) - O'Connor, Brenda; Dhuibhir, Pauline Uí; Higgins, Stephen; Balding, Lucy; O'Leary, Norma; Walsh, Declan
Abstract : Background: Insomnia involves difficulty with sleep onset, maintenance, early morning wakening or non-restorative sleep. Prevalence is 30%–75% in cancer. Consequences include fatigue and impaired memory or concentration. It is under-reported, overlooked and severely impairs quality of life. ?Subjective sleep diaries underestimate insomnia. Objective measurements previously required dedicated sleep laboratories. Wireless medical technology enables objective sleep measurement in the natural environment. Aims: Conduct a feasibility study to examine if a wireless monitor can measure sleep in cancer. Evaluate acceptability in: Patient Nurse Family Correlate objective device results with subjective reports. Methods: A prospective observational study recruited 10 consecutive hospice inpatients (IP) and 20 consecutive community participants (CP) with cancer. Insomnia Severity Index recorded subjective sleep pattern. Participants used a wireless non-contact bedside sleep monitor for 3 nights. Three insomnia features were examined (sleep onset, maintenance, early awakening). A daily sleep diary was completed. Acceptability questionnaires were completed by patient, nurse and family. Statistical analysis was undertaken with SPSS version 22. Results: The device successfully recorded sleep patterns in all 30 participants. Inpatients: Mean age was 63 years (range 47–61). 7/10 were positive for one or more insomnia features. Delayed sleep onset was most common (7/10). Community Participants: Mean age was 64 years (range 47–84). 15/20 were positive for one or more insomnia features. Fragmented sleep was most common. 14/20 recorded over 30 min awake overnight with more than 2 awakenings. Early morning wakening was not present in either cohort. Poor sleep hygiene was noted in community participants compared to inpatients. Correlation between subjective and objective measures was not significant (IP: p=0.07; CP: p=0.106). Patients, nurses and family members reported 100% device acceptability. Conclusions: A wireless bedside monitor effectively measures sleep in cancer. High patient acceptability supports clinical use. Cancer-related insomnia features were common in both cohorts. Objective measurements correlated poorly with subjective.